The semaphorin 7A receptor Plexin C1 is lost during melanoma metastasis - Lazova, Rossitza; Gould Rothberg, Bonnie E; Rimm, David; Scott, Glynis (The American journal of dermatopathology, 2009)
The transformation of normal melanocytes, or melanocyte stem cells, to melanoma, is a complex process involving multiple mechanisms. Loss of tumor suppressor proteins, which function as brakes on cell growth, migration, or cell survival, was recognized early on as an important mechanism for initiation and progression of melanoma. Semaphorins and their cognate receptors, Plexins and neuropilins, are involved in neuronal pathfinding, immune function, and tumor progression through effects on blood vessel growth and cell migration. Semaphorin 7A (Sema7A) is a membrane-linked semaphorin that is expressed by human keratinocytes, and we have shown that Sema7A binds to human melanocytes through beta1-integrins and the Plexin C1 receptor. Functional studies showed that Sema7A stimulates cytoskeletal reorganization in human melanocytes, resulting in adhesion and dendrite formation. Downstream targets of Plexin C1 signaling in human melanocytes include cofilin and LIM kinase II, both of which are critical mediators of cell adhesion and migration. In this report, we analyzed the expression of Plexin C1 using immunohistochemistry on sections of primary and matched metastatic lesions from 19 subjects and in a large melanoma tumor microarray. Our data show a significant loss of Plexin C1 in metastatic melanoma compared with primary melanoma, suggesting the possibility that the Plexin C1 receptor is a tumor suppressor protein for melanoma.